Référence multimodale dans les narrations d’enfants : les gestes servent-ils à clarifier les expressions référentielles ambiguës ? - Corrado Bellifemine; Camille Dupret (Discours)
Referential gestures emerge early during children’s development. Growing up, they gradually master several multimodal resources and elaborate more complex discourse, using referring expressions often accompanied by gestures that increasingly correspond to the linguistic context and specificities of the interactional setting. Narratives are a complex discursive genre in which the management of referential chains remains difficult for the child for a long time, and gestures may be used to clarify ambiguous referring expressions. We collected 16 narratives of French 7-9 year old children in two distinct interactional settings. 8 children produced narratives from a textless set of pictures visually shared with the observer, and 8 children recounted a story to their mother after watching a cartoon. The gestures associated to the mention of entities were analysed according to several parameters: the setting, the type of gesture, the form of the referring expression, the animacy of the referent, and the position on the referential chain. These factors were found to have little effect on the density of gestures produced. At the qualitative level, more iconic gestures were produced in the absence of the shared medium, especially when the referent was maintained, regardless of the animacy of the referent and the linguistic form chosen. On the other hand, in the presence of the set of pictures more deictic gestures were produced, especially with pronominal forms to maintain reference. Our results show that children are sensitive to the interactional setting and the knowledge shared with the interlocutor.